Intramolecular hydrogen bond improved durability and kinetics for zinc-organic batteries - Sun, Tianjiang (2024)
Organic compounds have the advantages of green sustainability and high designability, but their high solubility leads to poor durability of zinc-organic batteries. Herein, a high-performance quinone-based polymer (H-PNADBQ) material is designed by introducing an intramolecular hydrogen bonding (HB) strategy. The intramolecular HB (C=O⋯N-H) is formed in the reaction of 1,4-benzoquinone and 1,5-naphthalene diamine, which efficiently reduces the H-PNADBQ solubility and enhances its charge transfer in theory. In situ ultraviolet-visible analysis further reveals the insolubility of H-PNADBQ during the electrochemical cycles, enabling high durability at different current densities. Specifically, the H-PNADBQ electrode with high loading (10 mg cm-2) performs a long cycling life at 125 mA g-1 (> 290 cycles). The H-PNADBQ also shows high rate capability (137.1 mAh g-1 at 25 A g-1) due to significantly improved kinetics inducted by intramolecular HB. This work provides an efficient approach toward insoluble organic electrode materials.